The relationship between the result of FMS research and risk of sports injuries - Ulewski, D.; Weber-Nowakowska, K.; Gebska, M.; Zyzniewska-Banaszak, E.; Kolodziej, L. (Journal of Education, Health and Sport, 2019)
Physical effort is undoubtedly linked to human functioning. Daily activities, professional work and locomotion are basic signs of physical exercises. Civilization development has caused many changes in the lives of the population and the main reason for these changes is sedentary life. Hypokinesis leads to the general weakening of the body. Professional athletes belong to the group of people who are not exposed to changes related to sedentary lifestyle. However, they are more exposed to the occurrence of musculoskeletal injuries which are called sports injuries. Despite conducting regular periodic examinations and screening among athletes, the problem of prevention and the occurrence of the injuries has not been appropriately described. The objectives of the study were to assess physical fitness of a selected group of athletes using the Functional Movement Screen, to examine the correlation and statistical significance between the FMS score and the number of past injuries and to determine the need for prevention of sports injuries for athletes. The study involved 25 handball players from the Pogon Szczecin team in the years 2015 - 2017. The study consisted of two parts: author's questionnaire survey and FMS test. Statistical analysis of the results did not show any significant effect of FMS on the number of injuries in handball (r = -0,19). The main factor that affects the number of injuries is the long-term practice of players on handball courts (r = 0,54). Commonly known phenomenon among the players is participating in trainings despite damages and pain that results from the past injuries.